Reproductive Performance of Saanen Goats After PGF2α Intramuscular Injection in Correlation to Body Weight - Chomsiatun Nurul Hidayah; Aras Prasetiyo Nugroho; Dewi Puspita Candrasari (Faculty of Animal Science, Jenderal Soedirman University in associate with Animal Scientist Society of Indonesia (ISPI), 2022)
An experiment was conducted at Kalikesur Farm, Kedung Banteng, Banyumas to investigate the reproductive performance of Saanen dairy goats after PGF2α injection on different body weights. This experiment included twenty female Saanen goats at 2-3 years of age, 2-3 kidding periods, and varying body weights of 30 to 55 kg. All goats were intramuscularly injected by 2 ml PGF2α (LutalyseTM, Pharmacia and Upjohn Company, Pfizer Inc) in a double injection pattern, with 11-day interval to perform estrous synchronization. The variables on reproductive performance such as estrus onset, length of estrus, and intensity of estrus were measured and monitored twice a day at 6-10 am and 3-5 pm. Descriptive statistics and correlation analysis were conducted. Results demonstrated that body weight performed strong correlations with estrus intensity (r = 0.66) while the time for the first estrus (onset) has a negative moderate correlation with body weight (r = -0.47), a negative weak correlation was recorded between body weight and length of estrus (r = -0.17). Based on the results obtained, it can be concluded that the body weight of goats in the estrus synchronization program can be used to be an indicator of reproductive performance, especially in estrus intensity. This can help farmers to predict estrus behavior after PGF2α synchronization.